Optimizing postoperative outcomes following neoadjuvant chemotherapy and mastectomy with immediate reconstruction: A national analysis. Issue 5 (5th January 2023) - Thawanyarat, Kometh; Johnstone, Thomas; Rowley, Mallory; Navarro, Yelissa; Hinson, Chandler; Nazerali, Rahim S.
Abstract: Background: The optimal timing between last neoadjuvant chemotherapy (NAC) session and mastectomy with immediate reconstruction (MIR) procedures has sparse data to support optimization of postoperative outcomes. Current literature suggests that timing is not a predictor of complications in patients undergoing implant‐based reconstruction following NAC and other literature suggests guidelines based on tumor staging. To the best of our knowledge, this is the largest and most recent study characterizing the effect of time between NAC and mastectomy with immediate reconstruction on postoperative complications. Methods: Patients in the Optum Clinformatics Data Mart that underwent all billable forms of breast reconstruction following NAC were identified via CPT and ICD‐10 codes. Data concerning these patient's demographics, comorbidities, oncologic treatment, and outcomes were collected by querying relevant reports of CPT, ICD‐9, and ICD‐10 codes. To meet inclusion criteria, patients needed to have an encounter for antineoplastic chemotherapy within 1 year of their associated reconstruction. Patients with other invasive procedures unrelated to their mastectomy—reconstruction pairing within 90 days of reconstruction were excluded. Outcomes analysis was limited to the 90‐day postoperative period. The time between the last recorded chemotherapy encounter and breast reconstruction was computed. A multivariate logistic regression analysis was performed to ascertain the effects of age, race, coexisting conditions, reconstruction type (autologous or implant‐based), and time between NAC and reconstruction on the likelihood of any common postoperative complication occurring. Linearity of the continuous variables with respect to the logit of the dependent variable was confirmed. Odds ratios and corresponding 95% confidence intervals were calculated. Results: From over 86 million longitudinal patient records, our study population included 139 897 4371 patient records corresponding to 13 399 3759 patients who had NAC and breast reconstruction between January 2003, October 2015, and June 2019. Increased time between last antineoplastic chemotherapy and MIR reconstruction was a statistically significant, independent predictor of decreased complication likelihood. By contrast, autologous reconstruction, hypertension, and type II diabetes mellitus, and African American, White, and Hispanic race (relative to Asian) had statistically significant associations with increased complication likelihood. Waiting an additional day between a patient's most recent chemotherapy session and MIR reconstruction reduces the odds of a complication occurring by 0.25%. This corresponds to reduction in odds of complication occurrence of approximately 7% for each month between neoadjuvant therapy and breast reconstruction. Conclusion: Increased time between NAC and MIR immediate reconstruction decreases the likelihood of experiencing one or more postoperative complications. Ideal time delay between 4 and 8 weeks has been shown to provide the best benefit for future breast reconstrution outcomes. In consultation with the oncologist, this information can be used to balance postoperative complication risk with increased oncologic risk in delaying mastectomy with immediate reconstruction.